Evaluation of oral status in patients with Post-traumatic stress disorder during the war on Syria - بجك, هلا; عمار أمون (Latakia University Journal -Medical Sciences Series, 2023)
Introduction :PTSD is an anxiety disorder that results from exposure to a traumatic event such as terrorist attacks, war fighting.. PTSD patients are at risk of developing many health problems resulting from stress and tension. Objective: To assess the oral health status of PTSD patients who developed the disorder as a result of fighting and exposure to war stress in Syria. Materials and Methods: Intraoral clinical examinations were performed using the DMFT index, the level of oral health was assessed by using the Simplified Oral Hygiene Index (OHIS), and the Daily Dental Care Scale. Results: The mean value of the DMFT index in the patients group was 9.34±2.55, the average index value in the patients group was 2.91±0.98 , we observed a decline in the level of oral care among the members of the patients group, as 90% of them achieved grades 0 and 1 on the Davidson Oral Care Scale. Conclusion: Our study concluded that patients with ptsd in Syria suffer from poor oral health, and a decline in the level of oral care, the oral health of ptsd patients was worse than the control sample with a statistically significant difference.